Vascular dysfunction in sporadic bvFTD: white matter hyperintensity and peripheral vascular biomarkers - Min Chu; Deming Jiang; Haitian Nan; Lulu Wen; Li Liu; Miao Qu; Liyong Wu (Alzheimer’s Research & Therapy, 2024)
Abstract Background Vascular dysfunction was recently reported to be involved in the pathophysiological process of neurodegenerative diseases, but its role in sporadic behavioral variant frontotemporal dementia (bvFTD) remains unclear. The aim of this study was to systematically explore vascular dysfunction, including changes in white matter hyperintensities (WMHs) and peripheral vascular markers in bvFTD. Methods Thirty-two patients with bvFTD who with no vascular risk factors were enrolled in this cross-sectional study and assessed using positron emission tomography/magnetic resonance (PET/MRI) imaging, peripheral plasma vascular/inflammation markers, and neuropsychological examinations. Group differences were tested using Student’s t-tests and Mann–Whitney U tests. A partial correlation analysis was implemented to explore the association between peripheral vascular markers, neuroimaging, and clinical measures. Results WMH was mainly distributed in anterior brain regions. All peripheral vascular factors including matrix metalloproteinases-1 (MMP-1), MMP-3, osteopontin, and pentraxin-3 were increased in the bvFTD group. WMH was associated with the peripheral vascular factor pentraxin-3. The plasma level of MMP-1 was negatively correlated with the gray matter metabolism of the frontal, temporal, insula, and basal ganglia brain regions. The WMHs in the frontal and limbic lobes were associated with plasma inflammation markers, disease severity, executive function, and behavior abnormality. Peripheral vascular markers were associated with the plasma inflammation markers. Conclusions WMHs and abnormalities in peripheral vascular markers were found in patients with bvFTD. These were found to be associated with the disease-specific pattern of neurodegeneration, indicating that vascular dysfunction may be involved in the pathogenesis of bvFTD. This warrants further confirmation by postmortem autopsy. Targeting the vascular pathway might be a promising approach for potential therapy.